AN EXPOS OF MACHO CHARACTERS IN LOUIS LAMOURS WESTERN NOVELS; BRIONNE, THE CALIFORNIOS, AND HONDO - Syafri Badaruddin (Celt: A Journal of Culture, English Language Teaching & Literature, 2006)
Three novels entitled Brionne, The Californios, and Hondo written by Louis LAmour reveal the hard life in the western frontier of America which was still wilderness. LAmour shows the macho characteristics and attitudes through his macho characters. They apply the macho characteristics such as strength, bravery, virility, and manliness but remaining sensitivity. They also possess macho attitudes such as protective, honest, intelligent, with an aesthetic personality.